DIVERSITY AND CONSERVATION OF DIPTEROCARPACEAE IN THE PHOUXIENGTHONG NATIONAL PROTECTED AREA, LAO PDR - Xayyavong, Oumalay; Ngoc Hai, Tran (Journal of Forestry Science and Technology, 2020)
The Champasack’s Pouxiengthong National Protected area (CPNPA) is known as the repository of biodiversity. There are about 1,200 species of angiosperms in the area. The Dipterocarpaceae is among the dominant and important timber family in the study site. The species of this family are facing tremendous pressure due to habitat degradation, overexploitation and changing environmental conditions. Therefore, while exploring the floristic diversity of CPNPA, attempts were made to explore the Dipterocarpaceae diversity, distribution patterns, nativity, endemism, threat categories, and local uses. In the present study, distance sampling using line-transect was used to assess the species diversity, distribution and number of Dipterocarpaceae species in the CPNPA. Total 19 species of the Dipterocarpaceac representing 6 genera were recorded between 30- 300 m asl from CPNPA. Of these, 19 species were native, 2 species crictically endangered (10.53%), 4 species endangered (21.05%), and 10 species vulnerable (52.63%), 2 near threatened (10.53%). 1 least concern (5.26%). These species are represented in four forest types and are used for curing various diseases/ailments by the inhabitants of the buffer zone of CPNPA. Due to habitat degradation, the populations of these species are decreasing fast. The overexploitation, habitat degradation and changing environmental conditions of these species has led to rapid population depletion. Therefore, appropriate strategy has been suggested for the conservation and management of this family.